Peroxidasin is a novel target of NRF2 and influences epithelial-to-mesenchymal transition during oxidative stress - Hanmer, Kerry Leigh (My University, 2018)
Peroxidasin (PXDN) is a member of the haem-peroxidase protein family that contains a conserved peroxidase domain and additional extracellular matrix (ECM) protein binding domains. The functions of PXDN are still being identified although it has been shown to i) oxidise molecules by utilising hydrogen peroxide (H2O2), ii) facilitate formation of dityrosine cross-links and iii) catalyse sulfilimine bond formation within the basement membrane. PXDN expression is altered in various diseases such as cancer and therefore it is important to determine the regulators and functions of PXDN so as to identify new therapeutic targets. Since PXDN utilises H2O2, and previous studies have shown PXDN expression changes in response to H2O2, we hypothesised that the nuclear factor erythroid 2-related factor 2 (Nrf2) transcription factor is involved in PXDN regulation. Western blot analyses and immunofluorescence microscopy confirmed an increase in Nrf2 and PXDN expression during oxidative stress and upon treatment with Nrf2-specific inducers. Chromatin immunoprecipitation confirmed binding of Nrf2 to the PXDN promoter and luciferase assays indicated that Nrf2 binding to the PXDN promoter increases luciferase reporter gene expression. Mutagenesis of the potential Nrf2 binding site within the PXDN promoter significantly decreased gene expression thus confirming that Nrf2 regulates PXDN. A role for PXDN in cancer was then investigated and it was hypothesised that PXDN is potentially involved in epithelial-to-mesenchymal transition (EMT) during oxidative stress. Knockdown of PXDN expression (siRNA-mediated) was quantified by ELISA and preliminary assays were performed on wild type HeLa and SiHa cervical carcinoma cells in comparison to knockdown cells. PXDN knockdown in both cell lines resulted in decreased cell attachment. In HeLa cells, oxidative stress resulted in increased migration but PXDN knockdown abolished this effect. Oxidative stress in HeLa cells decreased invasion with PXDN knockdown resulting in a further decrease. PXDN knockdown in SiHa cells decreased cell migration and SiHa cells under oxidative stress exhibited increased invasion, which was reversed by PXDN knockdown. Reduced PXDN expression decreased the size and formation of 3D spheroids in both cell lines. In summary, Nrf2 binds the sequence, TGAATCTGGC, within the PXDN promoter and increases PXDN expression. Our preliminary findings also implicate PXDN in redox related EMT since PXDN knockdown caused significant alterations to key EMT features.
A Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2018
Keywords: Peroxidase; Horse-radish